Probing the Influence of the Ligands on the Magnetism of Dinuclear Manganese, Iron, and Chromium Complexes Supported by Aroylhydrazone. Issue 15 (23rd April 2014) - Domingo, Alex; Specklin, David; Rosa, Vitor; Mameri, Samir; Robert, Vincent; Welter, Richard
Abstract: The influence of aroylhydrazone and bridging ligands on the exchange coupling constant ( J ) of five dinuclear metal complexes is analyzed through ab initio calculations. The complete active space second‐order perturbation theory with localized orbitals offers not only estimates of J but also detailed information about the contributions of the molecular regions to the overall magnetism. This computational strategy is first validated for two previously reported ferromagnetic Mn III /Mn III and antiferromagnetic Fe III /Fe III complexes. Such calculations are extended to three new dinuclear complexes of Mn IV, Fe III and Cr III constructed with a chemically simpler ligand (HL ). We provide the synthesis and structural characterization (X‐ray diffraction crystallography) of these three new compounds. The HL ligand exhibits little electronic influence over the J value, but it directs the magnetic properties of the compound by conditioning the relative arrangement of the metal centres. Abstract : The influence of the different molecular regions of five dinuclear complexes constructed with aroylhydrazone ligands is explored through ab initio wave function calculations with localized orbitals. The role of the ligands is key to control the structure of the dimetallic core and, thus, determines the overall magnetism.